2000
DOI: 10.1111/1467-7679.00110
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals, Contagion and Currency Crises: An Empirical Analysis

Abstract: The 1990s will be remembered in economic history as a decade of currency crises. In September 1992 the exchange-rate mechanism of the European Monetary System came under attack. This was followed by the Mexican currency crisis of December 1994 and, more recently, the Asian and Russian crises. 1 Concern about the possibility of these crises spreading to other countries and the implications this might have for the conduct of monetary policy rekindled interest amongst economists and policy-makers in the determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Several subsequent studies also use probit (or logit) models. For example, Kruger et al (2000) use annual data for 19 developing countries spanning the period 1977-1997. They report that the current account deficit is the only variable that can be consistently linked to currency crises.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Several subsequent studies also use probit (or logit) models. For example, Kruger et al (2000) use annual data for 19 developing countries spanning the period 1977-1997. They report that the current account deficit is the only variable that can be consistently linked to currency crises.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Studies have used a probit model to estimate the probability of currency crises or currency crashes (Eichengreen et al 1996: Frankel andBerg and Pattillo 1999;Kruger et al 2000;Komulainen and Lukkarila 2003;Frankel 2005;Licchetta 2011;Furceri et al 2012;Zhao et al 2014). 6 Before examining the empirical literature, it is worth distinguishing between "currency crises" and "currency crashes" because these are two different concepts that are frequently confused.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using data for 20 developing countries, Kruger et al (2000) found that real exchange rate overvaluation and a dummy variable for a currency crisis in a foreign country had statistically significant effects on the probability of currency crises. Analyzing the data on 31 emerging market countries, Komulainen and Lukkarila (2003) found that the foreign debt of private companies and banks provides a good explanation of currency crises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This may be more likely in increasingly integrated international financial markets (International Monetary Fund (1999)). Kruger, Osakwe and Page (1998) consider that herd behavior leads to a concept they distinguish as unwarranted contagion, which occurs when a crisis spreads to another country that otherwise would not have experienced a speculative attack. This is consistent both with contagion as a residual (Masson (1999a,b,c)), and the definition used in this paper.…”
Section: Relationship With Existing Literaturementioning
confidence: 99%